1996
DOI: 10.1128/jb.178.23.6671-6676.1996
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal transfer of the 5-nitroimidazole resistance plasmid pIP417 from Bacteroides vulgatus BV-17: characterization and nucleotide sequence analysis of the mobilization region

Abstract: Three small 5-nitroimidazole (5-Ni) resistance plasmids (pIP417, pIP419, and pIP421) from Bacteroides clinical isolates are transferable by a conjugative process during homologous or heterologous matings. The mobilization properties of pIP417 originated from strain BV-17 of Bacteroides vulgatus were studied. The plasmid was successfully introduced by in vitro conjugation into different strains of Bacteroides and Prevotella species and could be transferred back from these various strains to a plasmid-free 5-Ni-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…In principle, resistance might also result from (i) diminished Mtz uptake or its active export (26,40), (ii) more efficient DNA damage repair (6,43), or (iii) enhanced scavenging of oxygen radicals that are produced according to certain models of Mtz activation (23,41). Of particular note are plasmid-and transposon-borne nim genes in certain Mtz r strains of Bacteroides fragilis that promote conversion of nitroimidazoles from prodrug to harmless amino derivatives, rather than to toxic nitroso radicals, and that thus confer resistance without loss of chromosomal nitroreductase gene function (5,46). DNA fingerprint and sequence analyses have indicated that each H. pylori clinical isolate differs genetically from most other independent isolates (1, 2).…”
mentioning
confidence: 99%
“…In principle, resistance might also result from (i) diminished Mtz uptake or its active export (26,40), (ii) more efficient DNA damage repair (6,43), or (iii) enhanced scavenging of oxygen radicals that are produced according to certain models of Mtz activation (23,41). Of particular note are plasmid-and transposon-borne nim genes in certain Mtz r strains of Bacteroides fragilis that promote conversion of nitroimidazoles from prodrug to harmless amino derivatives, rather than to toxic nitroso radicals, and that thus confer resistance without loss of chromosomal nitroreductase gene function (5,46). DNA fingerprint and sequence analyses have indicated that each H. pylori clinical isolate differs genetically from most other independent isolates (1, 2).…”
mentioning
confidence: 99%
“…Pairwise comparisons revealed that the unique mobilization polypeptide of pIP421 is definitively unrelated to the mobilization proteins of both plasmids pIP417 (25) and pBFTM10 (8) and also to those of plasmid pLV22a (15) and the transposon Tn4399 (13,14).…”
Section: ϫ7mentioning
confidence: 99%
“…The spread of the resistance among these significant opportunistic pathogens, which are responsible for various infectious diseases, could be explained by the fact that nim genes are usually found on mobilizable genetic elements, either in non-self-transferable plasmids or on the chromosome. Three such 5-Ni r plasmids (pIP417, pIP419, and pIP421) have already been characterized, and the mobilization properties of one of them, pIP417, has been fully analyzed (25). The mobilization region of plasmid pIP417 is closely related to that of both the erythromycin resistance plasmid pBFTM10 from Bacteroides fragilis (8) and pIP419 but not to that of pIP421.…”
mentioning
confidence: 99%
See 2 more Smart Citations